Kiai Leadership, Institutional Climate, and Santri Learning Motivation: Examining Reciprocal Determinism in Indonesian Pesantren Education - Moh Hanif Adzhar; Umil Mu’alimatun Muzaroh Fitroroh; Devi Widya Nirmala; Ummu Abiha Al Zahra; Muhammad Fatichul Irsyad (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2026)
Students' learning motivation can be shaped by the quality of the institutional environment and the leadership figures they encounter daily. Empirical studies that integrate Kiai leadership and institutional climate as simultaneous determinants within a single theoretical framework remain insufficient. This study addresses this gap by simultaneously and partially testing the influence of these two variables on students' learning motivation, grounded in Bandura's Social Cognitive Theory, which asserts that external environmental factors systematically shape an individual's motivational orientation. An associative quantitative approach was applied, involving 148 senior-level students at the Al-Madienah Denanyar pesantren in Jombang, selected through a proportionate stratified random sampling procedure. Data were collected via a Likert-scale questionnaire validated for reliability and validity, then analyzed using multiple linear regression. The results indicate that both variables simultaneously have a significant effect on students' learning motivation (R² = 0.240); however, when analyzed separately, only the institutional climate has a significant effect, while the leadership of the Kiai does not. These findings indicate that the institutional environmental conditions directly experienced by students have stronger predictive power over learning motivation than direct perceptions of the Kiai's leadership figure, thereby reinforcing Bandura's Social Cognitive Theory proposition that external environmental factors act as systematic determinants of individual motivational orientation. It is recommended that pesantren administrators prioritize strengthening the institutional climate, specifically in terms of relationships, discipline, engagement, and safety, as a key intervention in policies aimed at enhancing students' learning motivation.